P4P, Reputation and the Reduction of Costly Overprovision - Nadja Kairies (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2012)
We investigate the effect of reputational motivation on output in a scenario of overprovision of medical treatment. We assume that physicians differ in their degree of altruism, enjoy being perceived as good but dislike being perceived as greedy. We show that better reputational motivation unambiguously reduces the costs of healthcare provision and the magnitude of overprovision which in turn rises patient benefits. – – Wir untersuchen den Effekt von Motivation durch Reputation in einem Szenario der Überversorgung von medizinischen Leistungen. Wir nehmen an, dass Ärzte sich in ihrem Grad an Altruismus unterscheiden. Ärzte schätzen es als gut, jedoch nicht als gierig angesehen zu werden. Wir zeigen, dass bessere Motivation durch Reputation eindeutig die Kosten der Bereitstellung von Gesundheitsleistungen und das Ausmaß an Überversorgung reduziert, was wiederum die Patientennutzen steigert.
Keywords: D64; I11; I18; H42; 330; Altruism; performance; motivation